2007
DOI: 10.1007/s00436-007-0735-0
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infection of the appendix as a cause of acute appendicitis

Abstract: The association between parasitic infection of the appendix and acute appendicitis has been widely investigated. The aim of this retrospective study was to evaluate the prevalence of parasitic infection of the appendix in a tropical area at southeast Brazil and to assess its possible relation to acute appendicitis in surgically removed appendices. Of the 1,600 appendectomies performed during a 10-year period, 24 (1.5%) were found to have helminths within the appendix. Enterobius vermicularis was observed in 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 19 publications
4
79
0
4
Order By: Relevance
“…In one Brazilian study, 24 cases out of 1,600 appendectomies (1.5 %) with helminthes within the appendix were recorded during a 10-year period (Silva et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In one Brazilian study, 24 cases out of 1,600 appendectomies (1.5 %) with helminthes within the appendix were recorded during a 10-year period (Silva et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al (1989) in their review of 2,921 appendicectomies reported an incidence of 0.05 % Taeniasis. Silva et al (2008) in their retrospective study of 1,600 appendectomies performed during a 10-year period found a single case of appendicular Taeniasis. 2 cases were reported by Lejbkwicz et al (2002) and 3 cases by Khodjet El Khil et al (1980) while 1 case each were reported by Sartorelli et al (2005) and Payne et al (1970).…”
Section: Discussionmentioning
confidence: 99%
“…Durante su recorrido por el tracto gastro-intestinal, el parásito puede localizarse en forma inhabitual en el apéndice cecal, siendo en 1899 Still, quien describe por primera vez el compromiso apendicular por EB, variando ampliamente la frecuencia reportada a nivel mundial, entre 0,2-41,8%; en nuestra serie y al igual que en otros estudios la prevalencia alcanzó al 1,53% afectando mayormente al grupo de niños y adultos jóvenes (71% menores de 18 años) 9,14,17,19,20 .…”
Section: Discussionunclassified